Exploring why animal health practices are (not) adopted among smallholders in low and middle-income countries: a realist framework and scoping review protocol - Hidano, Arata; Holt, Hannah; Durrance-Bagale, Anna; Tak, Mehroosh; Rudge, James W. (Frontiers in Veterinary Science, 2022)
Background: Improving livestock health is considered critical to address poverty, malnutrition and food insecurity in low- and middle-income countries (LMICs). Modifications of livestock management practices is also increasingly recognized as an important strategy to mitigate global threats such as climate change and novel disease emergence. Smallholders are, however, under various constraints which prohibit them from altering health practices for livestock and little is known about how the adoption of these practices may be promoted. The proposed scoping review aims to systematically map evidence around ‘what practices are (not) adopted by smallholders under what circumstances, how and why?’. Method and analysis: We conducted initial scoping searches to broadly define types of animal health practices relevant for smallholders in LMICs and formulated search terms. A scoping review protocol was designed and registered. A systematic literature search will be conducted using electronic databases including CAB Abstract, Scopus, MEDLINE, EMBASE, and Web of Science Core Collection. Grey literature will be searched from AGRIS and Standards for Supporting Agricultural Livelihoods in Emergencies. Articles in English, pertaining to the animal health practices considered highly relevant will be considered eligible for inclusion. Articles will be screened at two stages by two independent reviewers; screening of titles, abstracts, and keywords, followed by full-article screening. The first reviewer will review 100% of the articles at both stages. The second reviewer will review a random sample of 20% of the articles at both stages. Any disagreements will be resolved using inputs from the third reviewer. A thematic analysis will be conducted to catalogue contexts and mechanisms for adoption and discussed under a realist framework. Discussion: Understanding of the mechanisms underlying the adoption of animal health practices by livestock smallholders in LMICs is crucial for successful implementation of interventions including those which are based on a One Health approach. This review will identify the extent of this knowledge across disciplines and inform future research priorities for the design of effective and feasible interventions which can contribute towards Sustainable Development Goal 2.